Business Cycles with Periodic Shocks in A Multi-Country and Multi-Regional Neoclassical Growth Model - Zhang, Wei-Bin (Asian Economic and Financial Review, 2017)
This paper generalizes the global economic growth model with any number of countries and each country with any number of regions recently proposed by Zhang (2016). Zhang’s model extends Uzawa’s two-sector growth model to a global economy for examining dynamic interactions between international trade, national and global growth, interregional migration, wealth accumulation and regional amenities. This study generalizes Zhang’s model by allowing all the time-independent parameters to be time-dependent. The generalization makes it possible to examine effects of any types of exogenous time-dependent shocks on the dynamic system cross regions and countries over time. We simulate the model with three countries and each country with two regions. We demonstrate the existence of equilibrium point and confirm (local) stability of the equilibrium point when all the parameters are time-independent. We conduct comparative dynamic analysis with regard to exogenous periodic shocks in the total factor productivity of regions’ capital good sectors, the total factor productivities of the service sectors, the propensity to save, the amenity parameters, and the propensity to consume housing. Our comparative analysis shows how business cycles are generated by periodic exogenous shocks.